Edukasi Partisipatif Pengelolaan Sampah Plastik Bagi Kader 'Aisyiyah sebagai Upaya Pelestarian Lingkungan Pesisir - A. Mappasere, Fatmawati; Haerana, Haerana; Khumaera, Izza (Jurnal SOLMA, 2024)
Background: Plastic waste is a serious global environmental issue, including in the coastal regions of Indonesia such as North Galesong Beach, Takalar Regency, South Sulawesi. This community service activity aims to enhance the knowledge and awareness of 'Aisyiyah cadres about plastic waste management, enabling them to become agents of change in minimizing coastal environmental pollution. Method: Participatory action research involving 32 'Aisyiyah cadres residing in the coastal area. The activity was carried out through initial assessment stages, planning, education implementation on March 2, 2024, evaluation, and reflection. The education was conducted using lecture methods, discussions, and audiovisual media. Result: Evaluation was done through pre-tests and post-tests, with results showing an average understanding score increase of 76% among participants. The success of this activity is supported by the effective delivery methods and the active involvement of partners from planning to evaluation. Conclusion: Recommendations for future activities include training in plastic waste processing, establishment of waste management institutions, education for the younger generation, collaboration with stakeholders, and further research to evaluate the long-term impact of the program. This activity is expected to increase community participation in environmentally friendly plastic waste management in the North Galesong coastal area.